PRINSIP DASAR EVALUASI DALAM PEMBELAJARAN PAI DI SD NEGERI 01 GINTUNG - Syukron Makmun; Ali Mubin (Universitas Muhammadiyah Tangerang, 2026)
This study discusses the principles of evaluation in Islamic Religious Education (PAI), as well as the concepts, functions, and objectives of evaluation, including the methods and techniques of evaluation in PAI education. This research aims to understand the basic concepts of evaluation in PAI learning at the elementary school level. The method used in this study is a qualitative method involving data collection in the form of texts and images rather than numerical calculations. The researcher hopes to provide solutions to fundamental problems in the education sector, particularly issues related to learning evaluation, by explaining the basic concepts of evaluation in Islamic Religious Education (PAI) learning. The research was conducted at SD Negeri 01 Gintung, Sukadiri District, Tangerang Regency. The data for this study were obtained from PAI teachers, the school principal, and sixth-grade students. Keywords: Basic Concepts of Evaluation, PAI Instructional. Studi ini membahas prinsip - prinsip evaluasi dalam pendidikan PAI serta konsep , fungsi , dan tujuan evaluasi , serta metode dan teknik evaluasi dalam pendidikan PAI.​​​​ Penelitian ini bertujuan untuk mengetahui konsep dasar evaluasi dalam pembelajaran PAI di Sekolah Dasar. Metode yang digunakan dalam penelitian ini adalah metode kualitatif yang melibatkan pengumpulan data dalam bentuk teks , gambar , dan bukan perhitungan. Peneliti berharap dapat memberikan solusi dari permasalahan fundamental dalam sektor pendidikan, yakni Masalah evaluasi pembelajaran yang menguraikan konsep dasar evaluasi dalam pembelajaran Pendidikan Agama Islam (PAI). Lokasi penelitian ini di SD Negeri 01 Gintung Kec. Sukadiri Kab. Tangerang. Data untuk penelitian ini diperoleh dari guru PAI , kepala sekolah , dan siswa kelas enam. Kata kunci: Konsep Dasar Evaluasi, Pembelajaran PAI